A New Physics-Inspired Discriminative Classifier - Mostafa Monemizadeh; Seyed Rouhollah Samareh Hashemi; Mohsen Sheikh-Hosseini; Hamed Fehri (AUT Journal of Electrical Engineering, 2024)
Concepts and laws of physics have been a valuable source of inspiration for engineers to overcome human challenges and problems. Classification is an important example of such problems that play a major role in various fields of engineering sciences. It is shown that discriminative classifiers tend to outperform their generative counterparts, especially in the presence of sufficient labeled training data. In this paper, we present a new physics-inspired discriminative classification method using minimum potential lines.  To do this, we first consider two groups of fixed point charges (as two classes of data) and a movable classifier line between them. Then, we find a stable position for the classifier line by minimizing the total potential integral on the classifier line due to the two groups of point charges. Surprisingly, it will be shown that the obtained classifier is actually an uncertainty-based classifier that minimizes the total uncertainty of the classifier line. Experimental results show the effectiveness of the proposed approach.